Effect of vertical inhomogeneity of the ridge keel filling on its freezing rate - O. M. Andreev (Лëд и снег, 2015)
Field data on ice ridges in the south-eastern and eastern parts of the Barents Sea collected by specialists of the Arctic and Antarctic Research Institute (AARI) in 2003–2007 has been used in attempt to understand the vertical inhomogeneity of the ridge keels filling. New ridges originated from one-year sea ice (with no consolidated layer or or less than 5–10 cm thick) have been analyzed. Reduction of original observations under certain additional assumptions has allowed formulating the vertical distribution of the ridge keel fill factor. This approximation has been applied in the one-dimensional thermodynamic ride model developed in AARI to simulate the ice ridges behavior in the Central Arctic and Arctic seas. The modeling of ridge freezing rates for different geographical sites has shown the more intensive freezing of ridge keels in initial stage than expected from previous modeling runs. The new results are consistent with field observations on consolidated layer thickness in ridges. Model calculations for a longer period show no big difference in results obtained with or without the approximation proposed.